PENGARUH KUALITAS PELAYANAN JASA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN STARLIGHT ORGANIZER BANDAR LAMPUNG - Resha Dwi Cahya; Iskandar Ali Alam (Jurnal Widya, 2023)
This study aims to determine the effect of Service Quality and Communication on the performance of Starlight Organizer Bandar Lampung employees. The population of this research is Starlight Organizer Bandar Lampung employees, with a sample of 30 people in the study. The method of analysis using multiple linear regression analysis. From the results of the study it was found that Service Quality and Communication together had a positive and significant influence on consumer satisfaction at Starlight Organizer Bandar Lampung, proven and acceptable to be true. It is hoped that with this research the Bandar Lampung Starlight Organizer can maintain the stability of Service Quality and Good Communication for customers so that it can improve employee performance at the Bandar Lampung Starlight Organizer.